Metal-free regioselective C-3 acetoxylation of N-substituted indoles: crucial impact of nitrogen-substituent - Soni, Vineeta; Patel, Ulhas N.; Punji, Benudhar (RSC Advances, 2015)
A metal-free method for the regioselective C-3 acetoxylation of the N-substituted indoles with PhI(OAc)(2) is described under mild reaction conditions. This method tolerates a broad range of functional groups with moderate to good yields. The pi-electron-deficient aryl-substituents on the N-atom of indoles and the acidic reaction medium remarkably favor C-3 acetoxylation.

Synthesis of quinoline-based NNN-pincer nickel(II) complexes: a robust and improved catalyst system for C–H bond alkylation of azoles with alkyl halides - Patel, Ulhas N.; Pandey, Dilip K.; Gonnade, Rajesh G.; Punji, Benudhar (Organometallics, 2016)
The quinoline-based pincer nickel(II) complexes κN,κN,κN-{R2N-C6H4-(μ-N)-C9H6N}NiX ((R2NNNQ)NiCl: R = Me, 2a; R = Et, 2b) were synthesized by the reaction of the ligand precursors (R2NNNQ)H (R = Me, 1a; R = Et, 1b) with (DME)NiCl2 in the presence of Et3N. Similarly, the pincer nickel(II) derivatives (R2NNNQ)NiX (R = Me, X = Br, 3a; R = Et, X = Br, 3b; R = Me, X = OAc, 4a) were obtained by treatment of the ligands (R2NNNQ)H with the nickel precursor (THF)2NiBr2 or Ni(OAc)2. All of these complexes were characterized by 1H and 13C NMR spectroscopy as well as by elemental analysis. Further, the molecular structures of 2a and 3a,b were elucidated by X-ray crystallography. Complex 2a is found to be an efficient catalyst for the direct C–H bond alkylation of substituted benzothiazoles and oxazoles with various unactivated alkyl halides containing β-hydrogens under mild reaction conditions. The catalyst 2a is very robust and was recycled and reused five times for the alkylation reaction without a decrease in its catalytic activity. Preliminary studies reveal that the catalyst 2a acts as an active catalyst and the alkylation reaction appears to operate via a radical pathway.

Copper- and phosphine-free nickel(II)-catalyzed method for C-H bond alkynylation of benzothiazoles and related azoles - Patel, Ulhas N.; Punji, Benudhar (Asian Journal of Organic Chemistry, 2018)
A phosphine-free nickel(II)-catalyzed method for the C(2)-H bond alkynylation of (benzo)thiazoles, (benz)imidazoles, and oxazoles is described. Well-defined and air-stable (Phen)NiCl2 catalyst efficiently catalyzes the coupling of diverse azoles with alkynyl bromides without the use of a copper co-catalyst, and the method tolerates synthetically important functional groups. Preliminary mechanistic studies on this Ni-II-catalyzed alkynylation emphasize the homogeneous nature of the catalyst, and rule out a radical manifold for the reaction. The synthetic utility of this Ni-catalyzed method is demonstrated by further functionalizing the alkynylated benzothiazoles to 3-methyl-2-(alkynyl)benzo[d]thiazolium salts that are known DNA cleaving agents.
Keywords: alkynylation; azoles; C-H activation; heterocycles; Nickel

Mechanism of nickel(II)-catalyzed C(2)-H alkynylation of indoles with alkynyl bromide - Khake, Shrikant M.; Jain, Shailja; Patel, Ulhas N.; Gonnade, Rajesh G.; Vanka, Kumar; Punji, Benudhar (Organometallics, 2018)
The nickel system (THF)(2)NiBr2/phen has recently been shown as an efficient catalyst for the C-H bond alkynylation of diverse heteroarenes with (triisopropylsilyl)alkynyl bromide via monodentate chelation assistance. Herein, we report an extensive mechanistic investigation for the direct alkynylation of indoles involving the well-defined nickel catalyst, which features a coordinative insertion pathway of alkynyl bromide with the Ni(II) catalyst. Catalytic relevant nickel complexes, (phen)NiCl2 (5), (phen)(2)NiCl2 (6) and [(phen)(3)Ni].NiCl4 (7) were isolated, and the complexes 6 and 7 were structurally characterized. Well-defined complexes were as competent as the in situ generated catalyst system (THF)(2)NiBr2/phen for the alkynylation of indoles. Various controlled studies and reactivity experiments were performed to understand the probable pathway for the alkynylation reaction. Kinetics analysis highlights that the complex (phen)NiX2 acts as a precatalyst, and the involvement of substrate indole and LiO'Bu are essential for the generation of the active catalyst. Deuterium labeling and kinetic studies suggest that the process involving C-H cleavage and carbo-nickelation of indole is a crucial rate influencing step. Reactivity study of various alkynyl compounds with nickel-species highlights a migratory insertion route for the reaction. DFT calculations firmly support the experimental findings and suggest the coordinative insertion pathway of alkynyl bromide rather than oxidative addition toward the nickel(II) center.

Mechanistic aspects of pincer nickel(II)-catalyzed C-H bond alkylation of azoles with alkyl halides - Patel, Ulhas N.; Jain, Shailja; Pandey, Dilip K.; Gonnade, Rajesh G.; Vanka, Kumar; Punji, Benudhar (Organometallics, 2018)
The quinolinyl-based pincer nickel complex, kappa(N),kappa(N),kappa(N)-{C9H6N-(mu-N)-C6H4-NMe2}NiCl [((NNNMe2)-N-Q)-NiCl; (1)] has recently been demonstrated to be an efficient and robust catalyst for the alkylation of azoles with alkyl halides under copper-free conditions. Herein, we report the detailed mechanistic investigation for the alkylation of azoles catalyzed by ((NNNMe2)-N-Q)NiCl (1), which highlights an iodine atom transfer (IAT) mechanism for the reaction involving a Ni-II/Ni-III process. Deuterium labeling experiments indicate reversible cleavage of the benzothiazole C-H bond, and kinetic studies underline a fractional negative rate order with the substrate benzothiazole. The involvement of an alkyl radical during the alkylation is validated by radical clock and external additive experiments. An active intermediate species ((NNNMe2)-N-Q)Ni(benzothiazolyl) (5a) has been isolated and structurally characterized. The complex ((NNNMe2)-N-Q)Ni(benzothiazoly1) (5a) is found to be the resting state of catalyst 1. Kinetic analysis of electronically different intermediates suggests that the step involving the reaction of 5a with alkyl iodide is crucial and a rate-influencing step. DFT calculations strongly support the experimental findings and corroborate an IAT process for the alkylation reaction.

Scope and mechanistic aspect of nickel-catalyzed alkenylation of benzothiazoles and related azoles with styryl bromides - Patel, Ulhas N.; Jagtap, Rahul A.; Punji, Benudhar (Organometallics, 2019)
Alkenylation of benzothiazoles and related azoles with alkenyl bromides is achieved employing the well-defined and air-stable nickel complexes, (bpy)NiBr2 and [Ni(bpy)(3)] [NiBr4], as catalysts. Numerous electronically distinct alkenyl bromides efficiently coupled with substituted benzothiazoles, oxazoles, and benzimidazoles under the catalytic conditions to afford 2-alkenylated azoles. An extensive mechanistic study of the alkenylation of benzothiazole using (bpy)NiBr2 highlights a single-electron transfer process for the reaction involving the two-step one-electron oxidative addition of alkenyl bromide. The substrate benzothiazole plays a significant and diverse role in the reaction, and C-H bond cleavage is reversible in nature. Detailed kinetic analysis and control reactivity studies are indicative of a Ni(I)/Ni(III) pathway for the alkenylation comprising the rate-influencing reductive elimination step.